Analysis of Timbre in Melodic Arrangements of Popular Minang Songs Using a Spectrum Analyzer - Robby Ferdian; Irdhan Epria Darma Putra; Hengki Armez Hidayat; Ressy Fitria; Revellame Revellame; Roald Marck J. (Journal of Urban Society's Arts, 2023)
Timbre is one of the main elements considered in musical arrangements, including contemporary Minang pop songs which have undergone significant development due to improvements in recording studio quality and increasingly qualified human resources. This study aims to describe the instrumentation and examine the characteristics of timbre in melodic instruments used in contemporary Minang pop song arrangements. Ableton Live 10 and Izotope Insight 2 software were used to analyze the audio spectrum produced by melodic instruments in recent Minang song arrangements. The results of audio processing using spectrum analyzer show that three main timbres of Minang songs are circulating and viral on social media: Acoustic Guitar, Bansi, and Overdrive Guitar. The first two instruments typically fill the melody line in the Intro, Interlude, and Coda, while the third instrument acts as a melody carrier in the transition part of the song. The instrumentation used in Minang song arrangements consists of acoustic instruments, specifically  Yamaha  guitars with Fishman Preamps, VST Instruments Sampletank2, and Real eight guitars. In this study, only two timbres were analyzed using the application: Acoustic Guitar and Bansi. The software analysis reveals that the two melodic timbres have unique characteristics formed by different overtone series formulas, with Acoustic Guitar having approximately 15 overtone pieces and Bansi having 8. Based on the results generated by the audio analysis application Izotope Insight 2, the timbre of guitar and bansi in contemporary Minang pop songs exhibit two unique characteristics. The guitar demonstrates a rich character with a significant number of overtone series at high frequencies. On the other hand, bansi tends to have a smooth and soft character due to its less dominant frequency points at each interval and lower amplitudes. Analisis Timbre pada Aransemen Melodik Lagu Minang Populer Menggunakan Spectrum Analyzer. Timbre merupakan salah satu elemen utama yang menjadi sorotan dalam menciptakan sebuah aransemen musik, begitupun dalam lagu pop Minang kontemporer yang telah mengalami perkembangan signifikan karena adanya peningkatan kualitas studio rekaman dan sumber daya manusia yang semakin berkualitas. Penelitian ini bertujuan untuk menggambarkan instrumen dan mengeksplorasi karakteristik timbre pada instrumen melodi yang digunakan dalam aransemen lagu pop Minang kontemporer. Penelitian ini menggunakan perangkat lunak Ableton Live 10 dan Izotope Insight 2 untuk menganalisis spektrum audio yang dihasilkan oleh instrumen melodi dalam aransemen lagu Minang terbaru. Hasil penelitian menunjukkan bahwa terdapat tiga timbre utama yang menjadi populer dalam lagu-lagu Minang masa kini yaitu: Gitar Akustik, Bansi, dan Gitar Overdrive. Dua instrumen pertama biasanya mengisi garis melodi pada Intro, Interlude, dan Coda, sedangkan instrumen ketiga berfungsi sebagai pembawa melodi pada bagian transisi lagu atau fill in. Instrumen yang digunakan dalam aransemen lagu Minang terdiri dari instrumen akustik berupa gitar dengan merk Yamaha dengan preamp Fishman, VST Instruments Sampletank2, dan gitar Real 8. Dalam penelitian ini, hanya dua timbre yang dianalisis menggunakan perangkat lunak yaitu: Gitar Akustik dan Bansi. Analisis perangkat lunak tersebut mengungkapkan bahwa dua timbre melodi memiliki karakteristik yang unik yang dibentuk oleh formula seri overtone yang berbeda, dengan Gitar Akustik memiliki sekitar 15 bagian overtone Series dan Bansi memiliki 8 Overtone Series. Berdasarkan sinyal audio yang dihasilkan oleh aplikasi, timbre melodi lagu Minang populer ditandai oleh gitar dengan warna  yang kaya dan Bansi dengan warna yang lembut dan halus. Selain itu, semua audio yang diperoleh dari sumber memiliki kualitas yang sangat baik.Timbre is one of the main elements considered in musical arrangements, including contemporary Minang pop songs which have undergone significant development due to improvements in recording studio quality and increasingly qualified human resources. This study aims to describe the instrumentation and examine the characteristics of timbre in melodic instruments used in contemporary Minang pop song arrangements. Ableton Live 10 and Izotope Insight 2 software were used to analyze the audio spectrum produced by melodic instruments in recent Minang song arrangements. The results of audio processing using spectrum analyzer show that three main timbres of Minang songs are circulating and viral on social media: Acoustic Guitar, Bansi, and Overdrive Guitar. The first two instruments typically fill the melody line in the Intro, Interlude, and Coda, while the third instrument acts as a melody carrier in the transition part of the song. The instrumentation used in Minang song arrangements consists of acoustic instruments, specifically  Yamaha  guitars with Fishman Preamps, VST Instruments Sampletank2, and Real eight guitars. In this study, only two timbres were analyzed using the application: Acoustic Guitar and Bansi. The software analysis reveals that the two melodic timbres have unique characteristics formed by different overtone series formulas, with Acoustic Guitar having approximately 15 overtone pieces and Bansi having 8. Based on the results generated by the audio analysis application Izotope Insight 2, the timbre of guitar and bansi in contemporary Minang pop songs exhibit two unique characteristics. The guitar demonstrates a rich character with a significant number of overtone series at high frequencies. On the other hand, bansi tends to have a smooth and soft character due to its less dominant frequency points at each interval and lower amplitudes.